Dampak Masuknya Imigran Timur Tengah terhadap Keamanan Manusia Domestik dan Respon Kebijakan Amerika Serikat Era Donald Trump - Lucitania Rizky; Heru Siswoyo Kurniawan Bin Supriyadi (LPPM Universitas Abdurrab, 2021)
The U.S anxiety about Middle Eastern immigrants became one of the main concerns of foreign policy in the Trump era. By using human security and foreign policy concepts as the analysis tools, this study aims at describing US foreign policy in Trumpâ€™s era as the response to the influx of Middle Eastern immigrants waves that threaten U.S domestic personal security. The policy issued by Trumpâ€™s era was inspirable from the Islamophobia perspective that resulted in contradictive foreign policy with previous governmentâ€™s era. This study adopts a descriptive-qualitative approach with secondary data collection techniques. This study found some strategies foreign policy from Trumpâ€™s era as agendas to improve and maintain U.S domestic security. Those are Border Security and Interior Enforcement and executive order â€œProtecting the Nation from Terrorist Attacks by Foreign Nationalâ€ through travel ban.